Determinants of Capital Structure of Chinese Listed Firms - Li, Mengdi (2018)
This paper aims to study and identify the determinants of the company's capital structure and analyze which capital structure theory is more relevant and applicable to Chinese listed companies. The sample for this study involves 56 Chinese listed companies from 2009 to 2016 in five industries in the Shenzhen stock exchange (SZSE) from the database CSMAR (China Securities Market and Accounting Research). The panel data regression has been used to analyze the impact of capital structure on the companies. The profitability, size, growth opportunities, tangibility, non-debt tax shields and inflation could be as the independent variables. The research is to test the relationship between six variables and two leverages. According to our research, most of the determinants follow the prediction of theories, such as size, growth opportunities, profitability and non-debt tax shields, but the tangibility has the different prediction. On the contrary, the inflation is proved to not have a significant sign with the long-term and short-term leverage, which means the inflation does not have any right to interpret Chinese companies financing option.